Accelerated weathering and soil burial effect on biodegradability, colour and textureof coir/pineapple leaf fibres/PLA biocomposites - Siakeng, Ramengmawii; Jawaid, Mohammad; Khan, Mohammad Asim; Siengchin, Suchart (MDPI, 2020)
Accelerated weathering and soil burial tests on biocomposites of various ratios of coir (CF)/pineapple leaf fibres (PALF) with polylactic acid (PLA) were conducted to study the biodegradability, colour, and texture properties as compared with PLA.The biodegradability of a lignocellulosic composite largely depends on its polymer matrix, and the rate of biodegradation depends on many environmental factors such as moisture, light(radiation), temperature and microbes. Biodegradation was evaluated by soil burial and accelerated weathering tests. Changes in physical and morphological properties were observed in the biocomposites after weathering. These results allowed us to conclude that untreated CF/PALF/PLA biocomposites would be a more favourable choice owing to their better biodegradability and are suitable for the suggested biodegradable food packaging applications.